Factors affecting the implementation of the village development plan deliberation (Musrembang) in Waeheru Village, Teluk Ambon District, Ambon City - Latuconsina, Nurainy; Khairunnisa, Atikah; Tehuayo, Johan (International research journal of management, IT and social sciences, 2022)
Community empowerment is the implementation of village government that realizes the community's active role to be responsible for the development of shared life. This phenomenon sometimes illustrates that planning does not involve community stakeholders in formulating development policies. Planning errors carried out in the field often cannot be implemented; this happens because the paradigm of thinking of the bureaucratic apparatus is attached to various forms of interests that cannot be separated. One form of reference that can be put forward here is the mechanism for deliberation on development planning. Musrenbangdes is a mechanism in determining development policies and programs that must involve stakeholders. Sometimes it does not describe the form of a forum that can accommodate all the community's aspirations. Communities that exist as stakeholders are often ignored so that the screening of community aspirations does not work well. For example, local organizations such as the SOA adat group, hamlet, RT, and community units are rarely involved in the Musrenbang mechanism at the local level. The problem is that the society that forms the dynamics of this interest is a collection of individuals who tend to be adaptive, who maintain socio-cultural values.